Enhancing Defect-Induced Dipole Polarization Strategy of SiC@MoO3 Nanocomposite Towards Electromagnetic Wave Absorption - Wang, Ting; Zhao, Wenxin; Miao, Yukun; Cui, Anguo; Gao, Chuanhui; Wang, Chang; Yuan, Liying; Tian, Zhongning; Meng, Alan; Li, Zhenjiang; Zhang, Meng (Nano-Micro Letters, 2024)
Defect engineering in transition metal oxides semiconductors (TMOs) is attracting considerable interest due to its potential to enhance conductivity by intentionally introducing defects that modulate the electronic structures of the materials. However, achieving a comprehensive understanding of the relationship between micro-structures and electromagnetic wave absorption capabilities remains elusive, posing a substantial challenge to the advancement of TMOs absorbers. The current research describes a process for the deposition of a MoO3 layer onto SiC nanowires, achieved via electro-deposition followed by high-temperature calcination. Subsequently, intentional creation of oxygen vacancies within the MoO3 layer was carried out, facilitating the precise adjustment of electromagnetic properties to enhance the microwave absorption performance of the material. Remarkably, the SiC@MO-t4 sample exhibited an excellent minimum reflection loss of − 50.49 dB at a matching thickness of 1.27 mm. Furthermore, the SiC@MO-t6 sample exhibited an effective absorption bandwidth of 8.72 GHz with a thickness of 2.81 mm, comprehensively covering the entire Ku band. These results not only highlight the pivotal role of defect engineering in the nuanced adjustment of electromagnetic properties but also provide valuable insight for the application of defect engineering methods in broadening the spectrum of electromagnetic wave absor ption effectiveness. SiC@MO-t samples with varying concentrations of oxygen vacancies were prepared through in-situ etching of the SiC@MoO3 nanocomposite. The presence of oxygen vacancies plays a crucial role in adjusting the band gap and local electron distribution, which in turn enhances conductivity loss and induced polarization loss capacity. This finding reveals a novel strategy for improving the absorption properties of electromagnetic waves through defect engineering. Highlights: 1 Oxygen-vacancy-rich SiC@MoO3 nanocomposite with strong reflection loss (− 50.49 dB at 1.27 mm thickness) and broadband absorption band (8.72 GHz at 2.68 mm thickness) were constructed via in situ etching strategy. 2 The presence of oxygen vacancy leads to an increased conductive loss and defect-induced dipole polarization, which plays significant role in attenuating the incident electromagnetic wave.